Environmental liability, imperfect information and multidimensional pollution control - Elga Bartsch (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
A well known result in the economics of tort law is that in the case of a unilateral stochastic externality both a negligence rule and strict liability are in general able to achieve socially optimal precaution. It will be shown in this paper that this equivalence result does no longer hold if imperfect information and multidimensional pollution control activities are considered. It will turn out that a negligence rule may in fact have an adverse effect on the incentives of a potential polluter, causing an uncertain environmental damage, to take appropriate precaution. The change in incentives can be attributed to two effects: immunisation from potential liability and sharpening of incentives for observable precaution diverting effort from unobservable to observable precaution. A standard of negligence tends to distort the choice among different > strategies available in reduction of environmental risks, when pollution control efforts are imperfectly observable to differing degrees. This distortionary effect prevails to an even larger extent if there is no uncertainty with respect to the findings of negligence. Hence, in contrast to one-dimensional models of uncertain negligence, the model presented in this paper implies that when the set of possible strategies in reducing environmental risk is somewhat richer than just a onedimensional decision, uncertainty in verifying the negligent behaviour may actually improve incentives to take preventive pollution control measures compared to a certain standard of due care. Moreover, the polluter's response to changes in the policy parameters are no longer clear-cut in the way that is indicated by the standard model. Under some circumstances, an increase in the standard of negligence may lead to a decline in the level of precautionary pollution control. Therefore, the environmental policy maker has to be very careful when deciding on an optimal second best policy consisting of a divergence of the standard of negligence from the socially optimal level.
Keywords: 330